Over‐the‐scope clip system: A review of 1517 cases over 9 years - Kobara, Hideki; Mori, Hirohito; Nishiyama, Noriko; Fujihara, Shintaro; Okano, Keiichi; Suzuki, Yasuyuki; Masaki, Tsutomu (Journal of gastroenterology and hepatology, 2019)
Rescue therapy for gastrointestinal (GI) refractory bleeding, perforation, and fistula has traditionally required surgical interventions owing to the limited performance of conventional endoscopic instruments and techniques. An innovative clipping system, the over‐the‐scope clip (OTSC), may play an important role in rescue therapy. This innovative device is proposed as the final option in endoscopic treatment. The device presents several advantages including having a powerful sewing force for closure of GI defects using a simple mechanism and also having an innovative feature, whereby a large defect and fistula can be sealed using accessory forceps. Consequently, it is able to provide outstanding clinical effects for rescue therapy. This review clarifies the current status and limitations of OTSC according to different indications of GI refractory disease, including refractory bleeding, perforation, fistula, and anastomotic dehiscence. An extensive literature search identified studies reported 10 or more cases in which the OTSC system was applied. A total of 1517 cases described in 30 articles between 2010 and 2018 were retrieved. The clinical success rates and complications were calculated overall and for each indication. The average clinical success rate was 78% (n = 1517) overall, 85% for bleeding (n = 559), 85% (n = 351) for perforation, 52% (n = 388) for fistula, 66% (n = 97) for anastomotic dehiscence, and 95% (n = 122) for other conditions, respectively. The overall and severe OTSC‐associated complications were 1.7% (n = 23) and 0.59% (n = 9), respectively. This review concludes that the OTSC system may serve as a safe and productive device for GI refractory diseases, albeit with limited success for fistula.